DEIKSIS PERSONA DALAM KUMPULAN CERPEN CORAT-CORET DI TOILET KARYA EKA KURNIAWAN - Debora Anggita; Hasnah Faizah; Silvia Permatasari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2025)
The purpose of this research is to describe the type of persona deiksis in the collection of short stories Corat-Coret di Toilet by Eka Kurniawan. This research is qualitative, this research does not only intend to describe a situation that takes place in the short story collection, but this research in addition to collecting data also analyzes, interprets, and concludes. This type of research aims to describe the deiksis of persona in a collection of short stories Doodles in the Toilet. The data collection technique used in this study is a technique that uses the Miles and Huberman model, namely data reduction which is an important selection activity, discarding the unused and classifying data according to the type and form of deiksis. Based on the results of the analysis of the use of persona deiksis in the collection of Short Stories Cartoons in Toilet by Eka Kurniawan, the type of persona deiksis found in this study is the first persona deiksis found in the collection of short stories Corat-Coret in Toilet by Eka Kurniawan is only a single form. The second person deiksis in the collection of short stories Doodles in Toilet by Eka Kurniawan, namely the singular and plural forms. The third persona deiksis in the collection of short stories Doodles in Toilet by Eka Kurniawan is a single form. The first single persona deiksis in the collection of short stories Corat-Coret di Toilet by Eka Kurniawan is the form of me and ku. The second single persona deiksis in the collection of short stories Corat-Coret di Toilet by Eka Kurniawan is the form of you and mu. The second plural persona deiksis in the collection of short stories Corat-Coret di Toilet by Eka Kurniawan is your form. The third single persona deiksis in the collection of short stories Corat-Coret di Toilet by Eka Kurniawan is the form of it. Keywords: Person Deixis, Collection of Short Stories, Corat-Coret di Toilet, Eka Kurniawan